Presence and leaching of bisphenol a (BPA) from dental materials - Rune Becher; Hanne Wellendorf; Amrit Kaur Sakhi; Jan Tore Samuelsen; Cathrine Thomsen; Anette Kocbach Bølling; Hilde Molvig Kopperud (Medical Journals Sweden, 2018)
BPA has been reported to leach from some resin based dental restorative materials and materials used for orthodontic treatment. To confirm and update previous findings, especially in light of the new temporary lower threshold value for tolerable daily BPA intake, we have investigated the leaching of BPA from 4 composite filling materials, 3 sealants and 2 orthodontic bonding materials. The materials were either uncured and dissolved in methanol or cured. The cured materials were kept in deionized water for 24 hours or 2 weeks. Samples were subsequently analyzed by ultra-performance liquid chromatography coupled to mass spectrometry (UPLC-MS-MS). The composite filling material Tetric EvoFlow® and the fissure sealant DELTON® showed significantly higher levels of BPA leaching compared to control samples for all test conditions (uncured, 24 h leaching and 2 weeks leaching). There were no significant differences in amount of leached BPA for any of the tested materials after 24 hours compared to 2 weeks. These results show that BPA is still released from some dental materials despite the general concern about potential adverse effects of BPA. However, the amounts of BPA were relatively low and most likely represent a very small contribution to the total BPA exposure.